(untitled) (Docentes 2.0 Journal, 2020)
The deployment that technology has had since the middle of the last century has generated new ways of understanding education and innovative ways of developing it. The increase of an academically more restless population, together with the impact of ICTs in the world, has led to the emergence and development of renewed models of instruction that are fostering new challenges and challenges in an educational environment, which has never been characterized by speed in the implementation of innovations.